Il costume fuori scena: testimonianze e documenti del progetto creativo di Adelaide Ristori - Niccoli, Bruna (Drammaturgia, 2024)
This essay investigates a unique actress’s wardrobe in the history of 19th century theatrical costume: Adelaide Ristori’s costumes exemplify the case of a leading actress who has trod the stages of major theaters worldwide. The plays she performed were an opportunity to create the basic types of stage costume: the costume of that period, for historical dramas, and the all’antica costume, for subjects of classical culture. The fate of the preserved stage clothes followed that of her archive, with her numerous scenic materials, part of Adelaide Ristori Archive since 1967, at the Museo Biblioteca dell’Attore in Genoa. This essay wants to go beyond the attributive aspect, relating to the manufacture and the play for which the costumes were born, to answer a more subtle question, which concerns their aesthetic conception and functionality for the show. In a historical phase in which the conception of the costume has not yet been subjected to the director’s vision, Ristori was able to manage an autonomous artistic space made up of personal choices, which we can reconstruct through the reading of the many documents preserved.